EFFECTIVENESS OF BEET JUICE ON INCREASING HEMOGLOBIN LEVELS IN PREGNANT WOMEN WITH ANEMIAAT KERTAJATI HEALTHCENTER IN 2024 (Proceedings OPTIMAL, 2025)
men Introduction. Anemia, especially in pregnant women, is still a classic problem that can never be treated and has serious impacts on the mother and baby. Anemia in pregnancy is a condition of pregnant women with hemoglobin (Hb) levels < 11g/dl. One way that can be done to increase the Hb levels of pregnant women is by consuming beetroot juice. The research aims to determine the effectiveness of beets in increasing hemoglobin levels in pregnant women with anemia at the Kertajati Community Health Center in 2024. Method. This research uses a pre-experimental research design in the form of one group pretest posttest. The population in this study was all anemic pregnant women in the working area of the Kertajati Community Health Center, totaling 66 people, the total sample was 40 people. This sampling procedure uses purposive sampling. Data analysis used univariate with central tendency distribution and bivariate using the sanded t- test. Results and Conclusions. The majority of Hb levels of pregnant women with anemia at the Kertajati Community Health Center before giving beets experienced mild anemia of. In the moderate anemia category (10 – 10.9 gr/dl). The majority of pregnant women at the Kertajati Community Health Center had normal anemia after giving beetroot. In the mild anemia category (11.90 – 14.00 gr/dl). Providing beetroot juice was significantly effective in increasing the Hb levels of pregnant women with anemia at the Kertajati Community Health Center in 2024, with a p value = 0.000 < 0.05. Efforts by health workers to try to apply the treatment technique of giving beetroot juice as an alternative medical treatment to treat anemia in pregnant wo